PENINGKATAN KEMAMPUAN DAN PENGETAHUAN DASAR BAGI ANAK JALANAN DI YAYASAN SAVE STREET CHILD TANGERANG SELATAN - Indah Rahayu Lestari; Rinny Meidiyustiani; Retno Fuji Oktaviani; Imelda; Qodariah (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
The high rate of population growth in big cities which is not matched by an increase in welfare, results in higher social inequality that occurs in the social environment. As the population density increases and is not followed by an increase in per capita income, the community bears a heavy burden in meeting their basic needs. There are children who come from underprivileged families so they do not get their right to education. This is what happened in the slum area where families mostly work as scavengers in the Pondok Ranji area, Bintaro, South Tangerang. This community service activity program for street children consisted of simple English for children, making various creative creations, and watching the Folklore film together, which was attended by 25 children ranging in age from 3 to 13 years at the Save Street Child Foundation, Pondok Ranji, South Tangerang. By increasing the capacity and basic knowledge provided, it is hoped that it will increase curiosity to continue to improve knowledge and skills and increase enthusiasm for children to go to school.